Birth intentions among US fathers with disabilities. Issue 3 (July 2021) - Namkung, Eun Ha; Mitra, Monika
Abstract: Background: Men's birth intention is an indicator of their sexual health and plays an important role for their child's health and development; however, birth intendedness in fathers with disabilities has been unknown. Objective: This study examines disparities in birth intendedness among fathers with and without disabilities and explores whether the differences vary by marital status or race/ethnicity. Methods: Data from the 2011–2017 National Survey of Family Growth (NSFG) were used to examine pregnancy intendedness for fathers with ( n = 380) and without disabilities ( n = 1, 324) about their last birth in the five years preceding the interview. Multinomial regression models estimated the odds ratios of fathers' disability status on birth intention controlling for covariates. Interaction effects of disability status by marital status or race/ethnicity were also tested. Results: Fathers with disabilities were 1.89 (95% CI = 1.21, 2.95) times as likely to report their last birth as unwanted versus intended compared to those without disabilities after adjusting for covariates. Although married fathers without disabilities were less likely to report unintended birth than their unmarried counterparts, the protective effect of marriage was not evident among fathers with disabilities. Conclusions: Disabled fathers are at a higher risk of unintended birth compared to nondisabled fathers. These findings highlight the need to increase access to family planning services for disabled men. Further research is needed to better understand the risk factors that contribute to disabled fathers' unintended birth and how these are linked to their child and family well-being.